Analysis of effect of shock-acoustic treatment regimes on wear resistance of steel 45 - S. B. Skobelev; G. G. Bury (Омский научный вестник)
The paper presents the results of experimental studies of the effect of shock-acoustic treatment regimes on the wear resistance of samples when tested in a friction pair steel 45 – Br AJ 9–4. The influence of the values of the total treatment factor on the microhardness and roughness of the treated surface is studied, and the dependence of the friction moment in the period of run-off on the values of the total processing factor is obtained. The rational values of the total treatment factor for steel 45 are determined, at which minimum wear of the samples during the run-in period is achieved.